THE IMPACT OF DIGITAL ENVIRONMENT ON CHILDREN AND RESPOND TO SOCIALLY UNACCEPTABLE BEHAVIOR - Miodrag Simović; Mile Šikman (Revija za kriminologiju i krivično pravo)
The influence of digital environment on the psychophysical development of children is becoming more and more dominant, which is supported by empirical indicators. The type and degree of influence can be different, and the consequence is always the same and is reflected in the harmful effects on the psychophysical development of children. At the same time, numerous studies on victims show that the real impact of high technology on the psychophysical development of children is much greater than that shown by the available data. The main reason for such a situation could be sought in the reasons for non-reporting of these behaviors by the victim or rather non-recognition of the harmful effects of high technology on the psychophysical development of children. To this, we can add the detrimental effects of secondary victimization, which often covers victims of crime. In this sense, the question arises as to how society can most adequately respond to these behaviors. Different models of prevention can yield promising results, but raise questions about protection of children’s rights, including personal data. On the other hand, criminal repression, as ultima ratio, has full justification for its introduction, but also significant limitations. This is why the subject matter of this paper is prevention and suppression of socially unacceptable behavior manifested by the use of high technology, regardless of whether children are victims or actors of such behavior.